Dupilumab and House Dust Mite Immunotherapy in Patients with Atopic Dermatitis: A Preliminary Study - Agnieszka Bogacz-Piaseczyńska; Andrzej Bożek; Magdalena Krupka-Olek; Aleksandra Kawczyk-Krupka; Jolanta Zalejska-Fiolka; Giorgio Walter Canonica (Vaccines)
Background: Severe atopic dermatitis (AD) is a complex disease requiring systemic treatment. This study aimed to assess the effectiveness of combined therapy consisting of dupilumab and sublingual dust mite allergen immunotherapy (SLIT-HDM) in patients with severe AD and HDM allergies. Methods: Patients diagnosed with severe AD were included in this randomised, placebo-controlled, double-blind 12-month trial; they received SLIT for HDMs and/or dupilumab for 12 months and were compared with patients on cyclosporine. The primary outcomes for the treatment arms were changes in the Eczema Area and Severity Index (EASI), body surface area (%BSA), and Investigator Global Assessment (IsGA) over 12 months. The secondary outcomes were the proportion of patients who achieved IsGA success and reduced medication scores. Results: Significant improvements were observed in all analysed groups after 12 months of therapy based on the EASI, %BSA, and IsGA. However, the most substantial changes were observed in the groups treated with dupilumab or a combination of SLIT-HDM and dupilumab. Additionally, the proportion of patients who achieved an IsGA reduction was significantly greater in the group receiving combination therapy than in the other groups (9/14 [64% of the group receiving SLIT-HDM] vs. 11/14 [73% of the group receiving dupilumab] vs. 15/17 [88% of the group receiving dupilumab and SLIT-HDM] vs. 7/13 [53% of the group receiving cyclosporine]) (p < 0.05). Conclusions: In patients with severe AD and HDM allergies, combination treatment with dupilumab and allergen immunotherapy for HDMs may increase the therapeutic benefit over treatment with these methods separately.